2010
DOI: 10.2527/jas.2009-2131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactation feed intake and creep feeding on sow and piglet performance1

Abstract: Recommended Citation Recommended CitationSulabo, R C.; Jacela, J Y.; Wiedemann, E J.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; and Dritz, Steven S. (2007) "Effects of lactation feed intake and creep feeding on sow and piglet performance," Kansas Agricultural Experiment Station Research Reports: Vol. 0: Iss. 10. Abstract AbstractA total of 84 sows (PIC, Line 1050) and their litters were used to determine the effects of lactation and creep feeding on sow and piglet performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 40 publications
7
50
3
3
Order By: Relevance
“…Differences of creep feed intake among treatments may not have been enough to affect sow performance. These results are in agreement with Sulabo et al [ 19 ], who also demonstrated the providing creep feed did not affect body weight or alter back-fat thickness.…”
Section: Discussionsupporting
confidence: 93%
“…Differences of creep feed intake among treatments may not have been enough to affect sow performance. These results are in agreement with Sulabo et al [ 19 ], who also demonstrated the providing creep feed did not affect body weight or alter back-fat thickness.…”
Section: Discussionsupporting
confidence: 93%
“…The failure of energy-dense, PRODUCT and OIL, to improve litter weight at weaning over that of CONTROL (Contrast I, P = 0.89) is not in agreement with previous research that reported increased litter gains when sows were fed energy-dense lactation diets [ 30 , 31 ]. However, this may be attributed to the sows’ ADFI, as low feed intakes inhibit litter gain [ 9 ]; sows in the experiment did not consume enough feed to obtain lysine intakes required to maximize litter growth, based on the estimations of Coma et al [ 26 ]. Coma et al [ 27 ] reported that modern, adult sows supporting litters of 10 piglets require 55 g/d of lysine to support 2.2 kg of litter growth per day.…”
Section: Resultsmentioning
confidence: 99%
“…Feed intake, or more specifically dietary energy intake, is closely related to both sow and litter performance [ 8 ]. A decrease in energy intake may inhibit litter growth potential and increase body weight loss of sows [ 9 ], whereas, litter gains were increased with increased dietary energy utilization in the sow [ 8 ]. Therefore, since it should be higher in energy content the extruded product’s use in lactation diets has been hypothesized to improve litter gains.…”
Section: Introductionmentioning
confidence: 99%
“…Data measurements and collection were conducted by the research team with the help of farm workers. The thickness of backfat was measured by using ultrasound (PIGLOG105, SFAK-Technology, A Mode Scanner, SFK Technology A/S Helver, Denmark) on the last rib (P2; 6.5 cm from the midline of the last rib) and operated by the same employee throughout the experiment according to the method of Sulabo et al [18]. Body weight of piglets were individually recorded on day of delivery, after cross-fostering and 7, 14, and 21 days of lactation to calculate litter weight and daily gain (ADG).…”
Section: Data Measurements and Collectionmentioning
confidence: 99%